Achieving the Main Goal of Sustainable Development by Enhancing the Green Entrepreneurship Spirit Through Community Development Study Center (Indonesian Journal of Devotion and Empowerment, 2022)
Community service aims to increase students' insight and skills, and the Kendal Center for Community Development Studies tutors on green entrepreneurship. Green Entrepreneurship answers today's new business challenges. Sustainable development and a green economy demand many things to change by building something and thinking about environmental sustainability. Service activities are carried out offline using lecture methods, discussions, and the introduction of green entrepreneurship techniques. The results obtained from the service are that participants are interested in learning more about the characteristics of green entrepreneurship and are ready to enter a new era for business that supports sustainable development and understands environmental problems. The student's readiness is proven by creating new concepts to improve old business concepts to making marketing techniques that are more environmentally friendly. Pengabdian kepada masyarakat memiliki tujuan untuk meningkatkan wawasan serta keterampilan siswa dan tentor Pusat Studi Bina Warga Kendal tentang kewirausahaan hijau. Kewirausahaan hijau menjawab tantangan bisnis yang baru saat ini. Pembangunan keberlanjutan dan ekonomi hijau menuntut banyak hal untuk berubah dengan membangun sesuatu juga untuk memikirkan keberlangsungan lingkungan. Kegiatan pengabdian dilakukan secara luring dengan metode ceramah, diskusi, serta pengenalan teknik kewirausahaan hijau. Hasil yang didapat dari pengabdian adalah peserta tertarik untuk mempelajari karakteristik kewirausahaan hijau lebih dalam dan siap memasuki era baru untuk bisnis yang mendukung keberlangsungan pembangunan serta mengerti masalah lingkungan. Kesiapan para siswa dibuktikan dengan pembuatan konsep baru guna memperbaiki konsep usaha lama hingga pembuatan teknik pemasaran yang lebih ramah lingkungan.